Cartas de Sêneca a Lucílio e a metáfora do teatro: uma análise da representação do tempo estóico romano no século I d.C. - Mesquita, Fabrício Dias Gusmão Di (2020)
In this dissertation, we intend to present how the Stoic Roman time was thought, analyzed and represented through metaphors by the Roman philosopher Lucio Aneu Sêneca (1-65 AD) in some of his Letters to Lucílio, during the principality of Nero. Stoicism was a philosophy founded by Zeno de Cício (14th-3rd century BC) in Athens in the so-called Hellenistic period. The philosophy of the Stoics was based on the maxim "live according to nature" and sought to achieve harmony with the cosmos or universal reason. Such principles served as guidelines for men of Classical Antiquity to conform to the designs established by fate (heimarméne, fatum) and to practice the philosophical teachings of stoicism to act virtuously. The search for wisdom was a constant in the work of Seneca, who in the writing of his letters represented the Roman uirtus and the passions (pathós, affectus) in order to lead his disciple Gaio Lucílio Junior to achieve a wise life. For Seneca, it was necessary to dominate the existential life span, representing, as in a theatrical metaphor, the events unfolded by universal reason in the flow of destiny. The past, the present and the future were associated with a cyclical temporality that from time to time was remade in the socalled Universal Conflagration (ekypirosis). Memory and hope could cause false representations of reality in the human spirit, thus distancing the individual from a life mediated by cosmic reason. Building a narrative using metaphors about theater and time, Seneca allows us to reflect on his time and how time was thought of in his philosophy, thus seeking to understand the problems related to human existence in Classical Antiquity.